Development of UMP runabout vehicle (URV) frame - Ang, Soon Tat (2007)
This project was carried out to develop a specific frame structure for UMP Runabout Vehicle (URV). In carrying out the project, the objective is to develop and analyze The UMP Runabout Vehicle (URV) frame. The URV frame structure had been involved in design and analysis. The material of URV frame had been use aluminum alloy plate. The application of URV will be widely used running in small area such as campus. The methodology of this project was design a new trend of the frame structure and modeling the concept by using CAD software. In this project, 3 generation of URV had been done. Finally, analyze the modeling by using FEA software. This thesis will discuss regarding to certain aspect such as the stress distribution, strain analysis, static displacement, deformation and design cheek for the 'model.